A casa da mãe de Deus comporta o (outro)mundo: dinâmicas geográficas no santuário de Fátima em Fortaleza-Ce - Cavalcante, Tiago Vieira (2011)
The actual work discusses the different relations in the surroundings of Nossa Senhora de Fatima Sanctuary, located in Fatima Neighborhood, Fortaleza – CE. We call such relations as geographic dynamics relating them to religion. For this, we take this religious place as “house of god’s mother”, considering the metaphoric-categorie “house” soaked in geographic density and multiscaled possibility in its relation with home and place. Bachelardian attitude to think space, reasonable for us with contribution of Eric Dardel and Martin Heidegger and others. This way, from the cultural approaching in geography, we think its spatiality in ambit of dwell, remitting it from the inner space of the follower to the relations realized by the sanctuary with the world. To understand it, were realized a compromised bibliographic and documentary survey, camp observing, interview with ecclesiastical minister, conversations with passers-by in the sanctuary and application of questionnaire among followers and traders. Although, we characterize the geographic dynamics mediated by the sanctuary as vertical (relation house-another world), horizontal (relation house-world) and relational (relation house-world-another world). This last effected with parties in every 13th day of each month, especially im May and October. The religious party happens as a social geographic potency, as join the vertical and horizontal dynamics together in a peculiar sacrum-profane instant. It’s done by feed backing and potentiating the symbolic and institutional representativeness which the sanctuary holds. The Fatima’s Sanctuary, so, is a place with a great special importance, through its representativeness in geographic dynamics which supports itself and the religiosity of thousands followers.